The Signification of Minh Lê and Dan Santat's The Blur - Khafi Alfara Prayudia Utomo (Fakultas Ilmu Budaya, 2026)
Children's literature serves not only as a source of entertainment but also as a medium through which cultural values, experiences, and social meanings are communicated. Among the various forms of children's literature, picture books are unique because they combine verbal and visual elements to construct meaning. Through the interaction of text and illustrations, picture books are capable of conveying complex ideas and experiences in a manner that is accessible to readers of different ages. One picture book that presents a distinctive portrayal of childhood is The Blur (2022), written by Minh Lê and illustrated by Dan Santat. The Blur tells the story of a child who appears to possess extraordinary abilities, such as a supersonic voice, enhanced hearing, fantastically elastic limbs, and even the ability to become invisible. These abilities are presented through humorous narration and exaggerated illustrations. However, beneath these seemingly fantastical descriptions lies a deeper representation of childhood growth and development. The story follows the child from infancy through various stages of childhood while simultaneously portraying the experiences of parents who attempt to understand, nurture, and keep pace with their child's growth. As a result, the picture book provides a rich source for examining how growth is represented through both verbal and visual signs. This study aims to analyze the representation of growth in The Blur by applying Roland Barthes' semiotic theory. Barthes' theory was chosen because it enables the researcher to explore multiple layers of meaning contained within signs. Through the concepts of signifier, signified, denotation, connotation, and myth, the study investigates how verbal and visual elements work together to construct meanings related to childhood growth and development. In addition to Barthes' semiotic framework, the study also draws upon developmental psychology DIGITAL REPOSITORY UNIVERSITAS JEMBER DIGITAL REPOSITORY UNIVERSITAS JEMBER x perspectives to establish a theoretical understanding of human growth and development. These perspectives help explain the physical, cognitive, emotional, and social changes that occur throughout childhood and provide a foundation for interpreting the signs identified in the picture book.
Finalisasi Maya_08 Juli 2026
Keywords: Signification; Growth; Picturebook